جهود أبي بكر الصديق في نشر الدعوة الإسلامية - غربي, نعيمة; مهاوات, سارة; شبروا, وورود (جامعة الوادي university of eloued, 2014)
ف هذا البحث دراسنا شخص ةٌ أب بكر الصد قٌ رضى الله عنه وقد تطرقنا إلى دراسة ح اٌة أب بكر الصد قٌ رض الله عنه نشأته وح اٌته وص فٌاته الخلق ةٌ والخلق ةٌ وكذالك تكلمنا عن إسلامه ورفقته لرسول الله صلى الله عل هٌ وسلم وعإلى زهده وتواضعه كما تطرقنا إلى الجهود الت قام بها أب بكر الصد قٌ من أجل الدعوة الإسلام ةٌ ونشر الد نٌ الإسلام كما تكلمنا أ ضٌا عن خلافته لرسول الله صلى الله عل هٌ وسلم وموقفه من حروب الردة وتصدي لها وأ ضٌا جهاده بماله ف سب لٌ الدعوة الإسلام ةٌ . Summary In this research, figure Abu BakrAlsidik friend may God bless him We have referred to the study of the life of Abu Bakr, may Allah be pleased with him growing up and his life and birth and birth Sifath, and also talked about his conversion to Islam and his companions of the Messenger of Allah, may Allah bless him and the High asceticism and humility as we dealt with the efforts made by Abu Bakr friend for Islamic Call and the dissemination of the Islamic religion also talked about his succession to the Messenger of Allah, peace be upon him and his position on the wars of apostasy and address them and also struggle with his money for the sake of the Islamic Call.
دعوة